STUDI KRITIS TERHADAP PEMIKIRAN HAJI MUHAMMAD SARNI ALABIO TENTANG ZAKAT DALAM KITAB MABA’ID ILMU FIKIH - Firqah Annajiyah Mansyuroh (Pascasarjana UIN ANTASARI Banjarmasin, 2020)
This title of this article is An Analysis of Critical Thought Haji Muhammad Sarni Alabio Concerning Zakat in Maba’id of Jurisprudence (Maba’id Ilmu Fikih). The purpose of this article was to assess the Haji Muhammad Sarni Alabio thinking about the establishment of zakat, legal istinbath methods used, the reason of his thought, as well as the relevance of thought Sarni the context of zakat in Melayu world and Indonesia. The results of the article showed that there are three important thoughts about zakat that are explained in the Maba’id of Jurisprudence which we can critically analyze as a criticism the extent to which the fiqh of zakat is relevant as applied science both past and present. First, the book only mentions zakat for plants and fruits by only mention the 10% without the 5%. Second, only plants that produce staples, dates and dried grapes, gold and silver are required to pay zakat. Third, the unclear nisab of gold and silver. Law istinbath method used is based on Mazhab Syafi’i but without a clear nash mention on the book Maba’id of Jurisprudence. The Maba’id of Jurisprudence is a work of Malay Jurisprudence that needs to be appreciated. However, in order to be relevantly studied, there should be editors who provide explanations of contemporary fiqh zakat.